Soil water thermodynamic to unify water retention curve by pressure plates and tensiometer - Braudeau, Erik; Hovhannissian, Gaghik; Assi, Amjad T.; Mohtar, Rabi H. (Frontiers in Earth Science, 2014)
The pressure plate method is a standard method for measuring the pF curves, also called soil water retention curves, in a large soil moisture range from saturation to a dry state corresponding to a tension pressure of near 1500 kPa. However, the pressure plate can only provide discrete water retention curves represented by a dozen measured points. In contrast, the measurement of the soil water retention curves by tensiometer is direct and continuous, but limited to the range of the tensiometer reading: from saturation to near 70-80 kPa. The two methods stem from two very different concepts of measurement and the compatibility of both methods has never been demonstrated. The recently established thermodynamic formulation of the pedostructure water retention curve, will allow the compatibility of the two curves to be studied, both theoretically and experimentally. This constitutes the object of the present article. We found that the pressure plate method provides accurate measurement points of the pedostructure water retention curve h(W), conceptually the same as that accurately measured by the tensiometer. However, contrarily to what is usually thought, h is not equal to the applied air pressure on the sample, but rather, is proportional to its logarithm, in agreement with the thermodynamic theory developed in the article. The pF curve and soil water retention curve, as well as their methods of measurement are unified in a same physical theory. It is the theory of the soil medium organization (pedostructure) and its interaction with water. We show also how the hydrostructural parameters of the theoretical curve equation can be estimated from any measured curve, whatever the method of measurement. An application example using published pF curves is given.